Deep Phenotyping of CD11c+ B Cells in Systemic Autoimmunity and Controls - Rincon-Arevalo, Hector; Wiedemann, Annika; Stefanski, Ana-Luisa; Lettau, Marie; Szelinski, Franziska; Fuchs, Sebastian; Frei, Andreas Philipp; Steinberg, Malte; Kam-Thong, Tony; Hatje, Klas; Keller, Baerbel; Warnatz, Klaus; et al. (Frontiers in Immunology, 2021)
Circulating CD11c+ B cells are a key phenomenon in certain types of autoimmunity but have also been described in the context of regular immune responses (i.e., infections, vaccination). Using mass cytometry to profile 46 different markers on individual immune cells, we systematically initially confirmed the presence of increased CD11c+ B cells in the blood of systemic lupus erythematosus (SLE) patients. Notably, significant differences in the expression of CD21, CD27, and CD38 became apparent between CD11c− and CD11c+ B cells. We observed direct correlation of the frequency of CD21−CD27− B cells and CD21−CD38− B cells with CD11c+ B cells, which were most pronounced in SLE compared to primary Sjögren's syndrome patients (pSS) and healthy donors (HD). Thus, CD11c+ B cells resided mainly within memory subsets and were enriched in CD27−IgD−, CD21−CD27−, and CD21−CD38− B cell phenotypes. CD11c+ B cells from all donor groups (SLE, pSS, and HD) showed enhanced CD69, Ki-67, CD45RO, CD45RA, and CD19 expression, whereas the membrane expression of CXCR5 and CD21 were diminished. Notably, SLE CD11c+ B cells showed enhanced expression of the checkpoint molecules CD86, PD1, PDL1, CD137, VISTA, and CTLA-4 compared to HD. The substantial increase of CD11c+ B cells with a CD21− phenotype co-expressing distinct activation and checkpoint markers, points to a quantitative increased alternate (extrafollicular) B cell activation route possibly related to abnormal immune regulation as seen under the striking inflammatory conditions of SLE which shows a characteristic PD-1/PD-L1 upregulation.